Transformation du travail, transformation du métier : quels impacts sur la santé des opérateurs et sur l’activité collective ? - Lucie Cuvelier; Sandrine Caroly (Perspectives Interdisciplinaires sur le Travail et la Santé)
This research is based on the analysis of an important organizational and technical change carried out in a sorting post office. It aims to characterize the impact of this change on the work activity and on occupational health. Several methods (observations, interviews and questionnaire) have been implemented to understand the consequences of this period on the health of operators and on the collective dimensions of work. The results show that this period was a period of instability during which the workers’ health has been affected. They also show that this change has impacted the collective strategies previously developed by operators. Giving space for discussions and leeway to operators during these changes appears to be essential.